Effect of HTST and Holder Pasteurization on the Concentration of Immunoglobulins, Growth Factors, and Hormones in Donor Human Milk - Escuder-Vieco, Diana; Espinosa-Martos, Irene; Rodríguez, Juan M.; Fernández, Leónides; Pallás-Alonso, Carmen Rosa (Frontiers in Immunology, 2018)
Donor human milk (DHM) is submitted to Holder pasteurization (HoP) to ensure its microbiological safety in human milk banks but this treatment affects some of its bioactive compounds. The objective of this work was to compare the effects of HoP and high temperature short time (HTST) treatments on some bioactive compounds found in DHM. A total of 24 DHM batches were processed in a continuous HTST system (70, 72 and 75ºC for 5 to 25 seconds) and by HoP (62.5°C for 30 min). The concentrations of immunoglobulins (Igs) A, G and M, transforming growth factor-beta 2 (TGF-2), adiponectine, ghrelin and leptin were measured using a multiplex system, whereas the concentration of epidermal growth factor (EGF) was determined by ELISA. In relation to Igs, IgG showed the highest preservation rates (87–101%) after HTST treatments, followed by IgA (54–88%) andIgM (25–73%). Ig retention after any of the HTST treatments was higher than after HoP (p < 0.001). Treatment times required to reduce the concentration of IgM by 90% (D-value) were 130, 88 and 49 s at 70, 72 and 75ºC, while the number of degrees Celsius required to change the D value by one factor of 10 (z-value) was 11.79ºC. None of the heat treatments had a significant effect on the concentrations of TGF-2, EGF, adiponectin and ghrelin. In contrast, leptin was detected only in 4 of the samples submitted to HoP, whereas it was present in all samples after the different HTST treatments, with retention rates ranging between 34 and 68%. Globally, the concentration of IgA, IgG, IgM and leptin in DHM was significantly higher after HTST pasteurization performed in a continuous system designed to be used in human milk banks than after the HoP procedure that is routinely applied at present.